Assessing the impact of the creative economy approach on economic growth: A case study of Pedekik Village - Ahmad, Kharisma; Nurlaila Putri, Silvi Alya; Nabawi, Putri Sani; Wahyuni, Annisa Sri; Nurhasanah, Elis (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2024)
This study aims to assess the impact of the creative economy approach on economic growth. However, the hypothesis testing results indicate that the influence of the creative economy on economic growth is not significant. This finding is supported by the results of simple linear regression analysis, which suggest a weak correlation between the creative economy and economic growth. It appears that the creative economy sector in the village of Pedekik lacks sufficient innovation, creativity, and novel inventions to effectively compete with evolving market trends. While it is believed that over time, the creative economy may gradually supplant commodities and natural resources as key contributors to the Indonesian economy, this study's findings do not support a direct influence of the creative economy on economic growth.